High-intensity interval training method in karate athletes: Can it improve power, agility, and endurance in the Kumite category? - Hadi; Yudhistira, Dewangga (UIR Press, 2023)
During a special period, physical exercise for Kumite athletes is targeted at developing the dominant physical condition. Arm muscular power, leg muscle power, agility, and anaerobic endurance are the dominant physical conditions in Kumite. The high-intensity interval training (HIIT) technique of physical exercise is in agreement with the characteristics of the energy system in Kumite. However, there are issues and contradictions in past research on its implementation. As a result, the purpose of this research was to put the HIIT training method to the test to develop muscle power in the arms and legs, agility, and anaerobic endurance in karate athletes in the Kumite category during the special preparatory periodization stage. This study employed an experiment using a one-group pretest-posttest design. The sample included 15 male and female Kumite athletes aged 20–25 years, weighing 50–80 kg, and standing 155–180 cm tall. Standing broad jump, two-handed medicine ball put, agility t-test, and running anaerobic sprint test were the instruments used. Interviews, questionnaires, and field tests were utilized to collect data. The data analysis technique employed descriptive analysis and the Wilcoxon nonparametric test. The overall value of Asymp.sig (2-tailed) was 0.001 to 0.009, according to the study's findings. The HIIT training method was found to have a significant effect on improving arm muscle strength, leg muscle power, agility, and anaerobic endurance in karate athletes in the Kumite category. Research has contributed to the sport of karate in the Kumite category through the application of training programs and models that correspond to the characteristics of the specific periodization. Subsequent research, of course, does not only focus on the special periods because other periods are also important.